UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SMP ISLAM MIFTAHUL HUDA CUGENANG CIANJUR - Musliadi, Musliadi; Ahmad Rifai Abun; Rita Linda (UNISAN JURNAL, 2025)
Research is an activity of collecting, processing, analyzing and presenting data systematically and objectively, to solve problems or test hypotheses. The purpose of this research is to find out and describe: The management function of the principal in improving teacher performance at Di Sekolah Dasar Islam Terpadu Al-’Arabi Cikarang Barat. As well as supporting factors and inhibiting factors for teacher performance at Di Sekolah Dasar Islam Terpadu Al-’Arabi Cikarang Barat, Jabung District, East Lampung Regency.The type of research used is qualitative research and is descriptive in nature, namely research that describes the function of school principal management in improving teacher performance at Di Sekolah Dasar Islam Terpadu Al-’Arabi Cikarang Barat, Jabung District, East Lampung Regency. Sources of data in this study are: (1) Primary data, consisting of school principals, deputy principals of Madrasahs, staff/employees, teachers; (2) Secondary data, obtained from library research and documentation. Data collection methods in this study are observation, interviews, and documentation. The method of data analysis is done by processing data (selecting, classifying, summarizing results, and making data reduction).The results of the study show that the principal has carried out the stages of the management function well from the planning stage to controlling, however, sometimes there are obstacles in the implementation, this is due to the lack of professional teachers, the lack of infrastructure, and the lack of teachers. understand lesson plans and are reluctant to make lesson plans, the teacher’s lack of awareness of discipline in teaching